Ghrelin in plants: What is the function of an appetite hormone in plants? - Aydin, Suleyman; Geckil, Hikmet; Zengin, Fikriye; Ozercan, H. Ibrahim; Karatas, Fikret; Aydin, Suna; Celik, Venhar (Elsevier Science Inc, 2006)
In the present work, we provide compelling evidence for the expression of a ghrelin-like peptide hormone that has only been associated with animals, in various plant tissues. Ghrelin, the appetite stimulating hormone, has been identified from a number of different species including humans, rat, pig, mouse, gerbil, eel, goldfish, bullfrog and chicken. The study here was conducted using an immunohistochemistry assay to screen whether plants have any ghrelin immunoreactivity. In this respect, Prunus x domestica L. and Marus alba were examined. Immunohistochemistry results showed that there is a strong human ghrelin immunoreactivity substance in the parenchyma cells of these plants. This was entirely unexpected since this hormone was considered to be present solely in animals. Thus, this study is the first to report the presence of a peptide with ghrelin-like activity in plants, a finding that has only been observed in the animal kingdom. RIA analysis confirmed that these plants contain significant amounts of this substance. Furthermore, reverse-phase HPLC analyses of plant extracts showed an elution characteristic of the peptide identical to that of human ghrelin. In general, fruit from both plants had higher levels of the peptide than the vegetative parts. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: ghrelin; peptide hormones; growth hormone release; growth hormone secretagogue receptor